2007
DOI: 10.1111/j.1600-6143.2007.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFNγ in Allograft Tolerance Mediated by CD4+CD25+ Regulatory T Cells by Induction of IDO in Endothelial Cells

Abstract: Regulatory T cells have been described to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 42 publications
8
58
0
Order By: Relevance
“…We previously showed in vitro and in vivo that regulatory CD4 ϩ CD25 ϩ T cells from tolerant recipients were able to stimulate donor-type ECs to express IDO, a molecule required for the establishment of tolerance, demonstrating an interplay between graft ECs and regulatory CD4 ϩ CD25 ϩ T cells for the maintenance of tolerance (10). Here, we also observed that regulatory CD4 ϩ…”
Section: Regulatory Cd4 ϩ Cd25 ϩ T Cells From Tolerant Recipients Enhsupporting
confidence: 66%
See 3 more Smart Citations
“…We previously showed in vitro and in vivo that regulatory CD4 ϩ CD25 ϩ T cells from tolerant recipients were able to stimulate donor-type ECs to express IDO, a molecule required for the establishment of tolerance, demonstrating an interplay between graft ECs and regulatory CD4 ϩ CD25 ϩ T cells for the maintenance of tolerance (10). Here, we also observed that regulatory CD4 ϩ…”
Section: Regulatory Cd4 ϩ Cd25 ϩ T Cells From Tolerant Recipients Enhsupporting
confidence: 66%
“…We demonstrated that following transfer, regulatory CD4 ϩ CD25 ϩ T cells accumulated in the new graft and induced the expression of IDO in graft ECs (10). Here, we also observed a specific expression of CLEC-1 in ECs in the new allogeneic graft following transfer of regulatory CD4 ϩ CD25 ϩ T cells from tolerant recipients (Fig.…”
Section: Cd25supporting
confidence: 60%
See 2 more Smart Citations
“…Previous studies demonstrated that concomitant interstitial fibrosis and inflammation in protocol biopsies obtained in the first year correlates with later allograft dysfunction and loss [25]. Finally, belatacept treatment allowed maintaining a stable number of FoxP3 + cells at tissue level which, in turn, could contribute to preserve in-situ tolerance mechanisms [26]. Although the levels of FoxP3 + -expressing cells were not statistically different at 12 months between both group specimens, CsA was associated with a significant decrease of FoxP3 + cell percentages when compared to pre-implantation levels, which is in agreement with a previous study where CsA and rapamycin were compared [27].…”
Section: Discussionmentioning
confidence: 99%